Re-introduction of a bioactive bacterial endophyte back to its seaweed (Ulva sp.) host, influences the host’s microbiome - Deutsch, Ynon; Ofek-Lalzar, Maya; Borenstein, Menahem; Berman-Frank, Ilana; Ezra, David (Frontiers in Marine Science, 2023)
Ulva is a commercially important marine macroalga. It hosts both epiphytes and endophytes. The latter are assumed to protect Ulva through secondary metabolites. Previously, we demonstrated bioactive endophytes from macroalgae with great potential to control diseases of aquaculture. In this study, we introduced a bioactive bacterial endophyte back into its original host (Ulva sp.) and demonstrated its survival over time in fresh and freeze-dried Ulva sp. We visualized the endophyte's location and survival in the seaweed using a Green Fluorescent Protein (GFP) reporter gene. The isolate colonized the intercellular space and survived for at least 5 months in fresh, and 12 months in freeze-dried algae, while maintaining its bioactivity against the aquaculture pathogen Streptococcus iniae. We studied the influence of the endophyte on the bacterial community in the Ulva sp. We found that once introduced, the endophyte significantly changed algal microbiota diversity and abundance. Two of Ulva's associated bacterial species were quantified over time, suggesting different trends in absolute abundance of these bacteria between treatments. To the best of our knowledge, this is the first report of the successful introduction of an endophytic microorganism into macroalgal tissue. These findings may be useful in applied research for the potential management of aquaculture diseases.